IMPLIKASI HUKUM INTERNASIONAL TERHADAP PEMUNGUTAN SUARA SISTEM NOKEN/IKAT DI PAPUA - Yusty Foxdey Rahawarin (PATRIOT, 2025)
The Noken/Ikat voting system reflects a recognition of Papuan traditions. This is important for maintaining cultural identity, but it needs to be aligned with appropriate legal regulations. The author uses a normative juridical approach, examining the application of rules or norms in positive law. The results of this paper: Voting using the Noken system has been legitimized by the Constitutional Court (MK) in Case Number 47-81/PHPU. A-VII/2009, which was then reinforced by regulations issued by the General Elections Commission (KPU), namely, General Elections Commission Decree Number 216 of 2024 concerning Amendments to General Elections Commission Decree Number 66 of 2024 concerning Technical Guidelines for the Implementation of Voting and Vote Counting in General Elections. Based on these regulations, the Noken/Ikat system is the result of "community agreement" or "acclamation." Recognition of indigenous peoples' rights to decision-making and political participation is regulated in Article 25 of the International Covenant on Civil and Political Rights (ICCPR), which was later ratified in Law of the Republic of Indonesia Number 12 of 2005. This regulation emphasizes the existence of two distinct entities: national law and customary law. In this context, the use of noken can be seen as a recognition of customary law operating alongside national law. Therefore, the state guarantees the right of everyone to participate in public affairs and to vote in free and fair elections. This includes recognizing voting methods appropriate to local culture. Therefore, elections using the noken system can support traditions and culture, increase public trust in the democratic electoral system, and enhance the political participation of indigenous peoples by ensuring that individual voices are properly represented and free from coercion.